IMPACT OF INTELLECTUAL CAPITAL ON PROFITABILITY, MARKET VALUE, AND PRODUCTIVITY OF THE LISTED BANKS: EVIDENCE FROM BANGLADESH - Hossain, Mohammad Kamal; Salam, Md. Abdus; Reza, Md Moslahur; Hasan, Md. Tamim (International Journal of Accounting & Finance Review, 2022)
This study examined the impact of intellectual capital and its elements (e.g., human capital, structural capital, and capital employed) on the profitability, market value, and productivity of all 30 publicly traded banks listed on the Dhaka Stock Exchange in Bangladesh. The study used unbalanced panel data with 146 observations for the period 2016–2020. Data was collected from the annual reports and the websites of the corresponding banks, as well as from the website of the Dhaka Stock Exchange. Multiple panel data regression models were employed to test the hypotheses studied. Intellectual capital was measured by the value-added intellectual coefficient (VAIC). This study found that banks with higher intellectual capital generated higher profits but lowered productivity; however, intellectual capital did not contribute to enhancing market value. Regarding the impact of subcomponents of intellectual capital, the study revealed that the human capital of the banks being examined enhanced profits but lowered productivity, with no impact on market value. Surprisingly, banks with higher structural capital had lower profitability but no influence on their market value or productivity during the study period. While capital employed was not found to affect the profitability, market value, or productivity of the sample banks in Bangladesh. The findings of the study suggest that the listed banks in Bangladesh failed to exploit intellectual capital well enough to gain a competitive advantage.JEL Classification Codes: E22, G32, O34, O16.